Peran Tuan Guru sebagai Opinion Leader dalam Pilihan Politik Masyarakat Dusun Kapek, Desa Gunungsari, Kecamatan Gunungsari - Ihsan Hamid; Wahyu Trisno Aji; Lara Aprilia (Universitas 45 Surabaya, 2024)
This research is motivated by the role played by Tuan Guru in Kapek Hamlet, Gunungsari Village, Gunungsari District, especially in the context of the local community's political choices. In Kapek society, Tuan Guru is respected because he is considered an influential religious figure. Kapek Hamlet is surrounded by two Islamic boarding schools, namely Az-Ziziyah Islamic boarding school and Ad Dinul Qayyim Islamic boarding school. Tuan Guru's role there is very diverse; as the main mover in the spread of Islamic teachings, also active as an opinion leader, providing social guidance. The research aims to explore in depth how the role of Tuan Guru influences political decisions among local communities. This research uses descriptive qualitative methods. The research results show that Tuan Guru's role as an opinion leader tends to focus on moral focus and creating conducive democratic elections. However, Tuan Guru is not directly involved in practical politics and does not impose political choices on the community. They prioritize individual freedom of choice, in accordance with democratic principles and the teachings of the Islamic religion.